Analysis and design of nonlinear control system via gain scheduling - Daw Khine Wut Hmone (2008)
The analysis and design of nonlinear control system is reported. A straightforward approach to design nonlinear controllers is to linearize the nonlinear model at the equilibrium point. Local Model Networks (LMN), as well as Local Model Networks, Local Model Controllers and Observer-based Local Model Control are described.